Studies of Vernacular Gyumri: from a future book - Ivanov, Andrei (project baikal, 2019)
Architectural and environmental peculiarities of the city of Gyumri (former Alexandropol, Leninakan) lie in the vernacular – a thick middle layer of historical “architecture without architects” built by local skilled bricklayers from the local material, black tuff. In the beginning of the article the author presents his new theoretical concepts of the living vernacular city and vernacular ensemble. Then the studies speak about peculiarities of the emergence of vernacular architecture at different stages of urban formation and its present-day existence. High grand arch-shaped portal gates – the archetype of the city environment of the Alexandropol period – perform important symbolic functions and play a key role in the environmental entourage of many Armenian films. The process of reproduction of the vernacular environment in the socialist and post-Soviet periods is shown by the examples of the buildings of the 1950s and the 2000s.
Keywords: vernacular; living vernacular city; vernacular ensemble; black tuff; master